Socio-Economic Background of Women Entrepreneurs on Small & Medium Enterprises in Panipat District, Haryana - Meena Devi (International Journal on Economics, Finance and Sustainable Development, 2022)
Entrepreneurship is an important factor mentioned above in community development. Business is the key to economic growth in the nation. Entrepreneurship plays a major role in developed countries. Small and medium enterprises offer great job opportunities in the community. Women have been successful in breaking their confinement within the walls of their homes by accessing a wide range of professionals and services. Sustainable economic growth and social justice, the socio-economic status of women must be improved as well as that of men. Social and economic freedom gives women the right to control the development of their lives. Entrepreneurship enhances the social status of women. The work of an entrepreneur depends on many different social, economic and psychological factors. Therefore, in any effort made to understand the business function among women, an analysis of their socio-economic status or status is required. Small and medium enterprises often contribute to local / rural economic development. The study aims to empower women in business and the socio-economic base of women entrepreneurs in the Panipat region, Haryana.